Fatty Acid, Tocopherol and Sterol Contents of Forest Pine Seed Oil - Musa Özcan, Mehmet; Matthaus, Bertrand (Asian Journal of Chemistry, 2013)
Pine seed (Pinus pinea L.) oil was evaluated for oil content, fatty acid composition, tocopherol and sterol contents. The main identified fatty acids were palmitic acid (4.43 %), oleic acid (18.78 %), linoleic acid (60.39 %) and linolenic acid (6.94 %). The major tocopherols of seed oil was a-tocopherol (5.38 %) and g-tocopherol (37.46 %). The total tocopherol content had 43.88 mg/100 g. The sterol contents of pine seed oil were established as 68.80 % b-stosterol, 10.66 % campesterol and 15.02 % 5-avenasterol. The total sterol was determined as 5868.39 mg/kg.